Factors Influencing Tuberculosis Knowledge among TB Patients in Gakenke District, Rwanda - Innocent Hakizimana; Erigene Rutayisire (Journal of Public Health International, 2020)
Knowledge of tuberculosis has been shown to influence health seeking behaviour. The study aim was to assess knowledge of tuberculosis and identify the associated factors. This study was a cross sectional descriptive research design with quantitative approach. The target population was the TB patients visited health facilities in Gakenke District. A sample of 376 TB patients was randomly selected from three health centers. Interview-administrated structured questionnaire was used to collect data from 376 TB patients. Data was analyzed with SPSS-version 22. The study protocol was approved by Mount Kenya University Rwanda. The majority of respondents 71.0% were male, 51.6% were aged 45 years and above, 81.9% were married, and 65.2% had completed primary education. Few respondents identified a germ as the cause of TB (24.7%). This study revealed that 54.3% of TB patients had good knowledge about TB. The findings from multivariate analysis show that male were three times more likely to have good knowledge about TB compared to female (AOR=3.31, 95%CI: 1.98-5.53, p<0.001). Compared to TB patients aged 45 years and above, respondents aged 25-34 years old were more likely to have good knowledge about TB (AOR=38.71, 95%CI: 9.22-162.48, p<0.001). TB patients who live between 2-5 km from nearest health facility were more likely to have good knowledge about TB compared to those who live at more than 5 km (AOR=33.58, 95%CI: 14.95-74.40, p<0.001). The ministry of health and other stakeholders in health sector need to continue the interventions that aim to reduce TB infection.
Keywords: Tuberculosis